O ensino da língua materna sob o prisma da educação linguística - Gomes, Agnelly Palitot (2016)
This research deals with an investigation through a sociolinguistic interventional proposal which sought to discover how students can appropriate a language education, and thus, instrumentalize them for the use of language, including variants. This research was performed in the Portuguese Language course with students from the 7th grade of a public school in Cabedelo, Paraíba. We emphasize the importance of identifying the adequacy of the language in different social contexts considering the standard norm not as the only variety to be studied in the classroom but as an additional possibility of language use. Therefore, we study the Bortoni-Ricardo Sociolinguistic Theory that brings a teaching proposal focused on Linguistic Education. We still use other authors who also refer to the theme such as Cavalcante (2014), Bagno (2007), Antunes (2007), Faraco (2002) and documents such as PCN (Brazil, 1998). This theory promotes spaces for different discourses that lead the student to expand their language skills through the acquisition of new expressive resources aiming to bring students to a reflection about these linguistic aspects in the educational process, focusing on teaching the mother tongue, considering the language experiences that students bring to the school environment and contributing to improve student interaction with the environment in which it is inserted since such theory considers the relationship between language and society. As a methodological procedure, the study was made feasible through an action research in order to propose direct intervention in the context and in relation to the subjects surveyed. In this sense, five students who participated in elaborated exercises containing the popular registry and the formal use of the language constituted the corpus of the analysis. The results obtained allow us to recognize the linguistic heterogeneity and point to the need to stimulate, in the mother tongue’s classes, a knowledge of the sociolinguistic varieties; As well as for the accomplishment of didactic-pedagogical procedure that contribute to deconstruct the linguistic prejudice still latent in our society.